Technological Maturity and its role in reinforcing the quality of auditing: An analytical study in Iraqi audit offices (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This paper discusses the role of Auditors' Technological Maturity in reinforcing the quality of auditing profession, through focusing on the concepts of Technological Maturity and quality of auditing profession, as well as designing a proposed model for Technological Maturity which includes five evolutionary and sequential stages, and this proposed model would contribute to reinforce the quality of auditing. This proposed model will be employed in the field of auditing profession because the importance of the development and investment in this profession and the importance of the need for specialized knowledge in Information Technology, and the result of a proposed model is development of technological knowledge for the auditor to reach him to the highest stage of maturity which is creativity and excellence through drawing a roadmap that enable the auditor to develop and improve his technological knowledge. This paper has reached several conclusions, the most important of which: there is a significant and positive effect of Technological Maturity in reinforcing the quality of auditing.